(3GdHfjI GdYGedjI debjGS GdbhI GdJfXjejI ddbGOI GdEOGQjjfs - (3Hf YeQ(B, (3aGWfI s ((3YeGfs (3OGQ GdCjGe ddfTQ hGdJhRjYs, 2022)
(3jgOa gPG GdcJGH Edi GSJcTGa eaghe GdbhI GdJfXjejI ddbGOI GdEOGQjjf hJMOjO HfjJg GdYGedjI(B. (3jHOC GdcJGH HJbOje eONd YGe deaghe GdbjGOI hGdbhI GdJfXjejI, MjK jhVM CgejI gGJjf GdeaGgje aj SjGb GdefXeGJ(B. (3Ke jfJbd GdcJGH Edi JMdjd GdYdGbI Hjf GdbhI GdJfXjejI hGdELQGAGJ GdejOGfjI GdJj jbhe HgG GdbGOI, hcjajI JCKjQ gPg GdbhI Ydi GJNGP GdbQGQGJ hJfajP GdNWW(B. (3jTed GdcJGH cPdc OQGSI JaUjdjI ddHfjI GdYGedjI debjGS GdbhI GdJfXjejI, MjK jJe JMdjd GdYfGUQ GdeNJdaI GdJj JTcd gPg GdbhI hcjajI JaGYdgG eY HYVgG GdHYV(B. (3jSYi GdcJGH Edi JbOje age CYeb dWHjYI GdbhI GdJfXjejI hcja jecf bjGSgG hJWhjQgG(B. (3haj GdLRA GdCNjQ ef GdcJGH, jJe YQV fJGFL GdOQGSI hefGbTJgG(B. (3jJe JMdjd GdHjGfGJ GdJj Je LeYgG ef NdGd JWHjb GdebjGS Ydi YjfI ef GdbGOI GdEOGQjjf, hJbOje GSJfJGLGJ Mhd GdHfjI GdYGedjI ddbhI GdJfXjejI(B. (3jSGge gPG GdcJGH aj JWhjQ GdCOhGJ hGdeaGgje GddGReI dJbjje GdbhI GdJfXjejI ddbGOI GdEOGQjjf hJMSjf COGFge(B.s
Keywords: (3GdbjGOI GdEOGQjIs